ANALISIS KAPASITAS INFILTRASI: STUDI KASUS GENANGAN BANJIR PADA DAERAH ALIRAN SUNGAI UNUS KOTA MATARAM - Fahmi, M. Arifudin; Syakirin, Syakirin; Edelweis, Edelweis (Yayasan Nusantara Hasana Berdikari, 2026)
The Unus sub-watershed in the Sandubaya, Cakranegara, and Mataram districts of Mataram City plays a crucial role in the hydrological cycle, particularly in the process of rainwater infiltration. This study aims to identify and analyze soil infiltration capacity in the area, review soil conditions, infiltration rates, and identify factors contributing to frequent flooding. The research method involved measuring infiltration rates at various points using a Double Ring Infiltrometer and analyzing infiltration capacity using the Horton method. The results showed that the average infiltration rate in the Unus Watershed (DAS) was 16.38 cm/hour, which is categorized as fast. The correlation analysis between the Horton method and field testing showed a very strong relationship, with an average correlation coefficient of 0.880, indicating that this method can be used to estimate infiltration capacity in the study area. Furthermore, the analysis showed that the average infiltration coefficient in the Unus Watershed was 0.892, or 89%, with an average infiltration rate of 0.024 m3/hour. The main factors influencing infiltration rate are soil water content and soil type, with soil with lower water content tending to have higher infiltration rates. The dominant soil types in the Unus Watershed are sand and clay, with sand representing 43.13% and silt accounting for 48.94%. The results of this study can inform more effective water management strategies, including land-use planning, vegetation maintenance, and drainage infrastructure development to reduce the risk of flooding in the Unus Sub-Watershed.